Jual Beli dengan Sistem Hutang di Pasar Tradisional dalam Perspektif Hukum Perdata - H. Syamsul Munir (Fakultas Ekonomi dan Bisnis Islam, 2019)
Debt trading in traditional markets with a nominal value of Rp. 1,000,000 (one million rupiah) down is usually done by recording under the hand. The seller emphasizes the element of trust rather than the element of legal proof. The process of buying and selling is fast, simple and if it is implemented with accounts receivable debt that is done simply, if the debt is stalled, intensive collection is carried out and the seller will receive it if paid in installments or in installments. In the process of payment the merchant does not provide interest expense or operating expenses due to the collection. If there is a debt dispute, the settlement is carried out in a family manner without involving law enforcement. Bad debt is certainly a calculation for traders who dare to pay off their merchandise. The factor of bad debt is usually not more than 20% of the total debt - the debt that must be paid by buyers with the debt system. Therefore the process runs in such a way and is considered natural. So the customary law factor that debt must be paid and the legal factor of trade that if you don’t pay the debt will sin more debt for the parties than the legal proof factor.